Keterampilan Komunikasi Ilmiah Siswa pada Materi Kalor dan Perpindahan Kalor: Analisis Spektor-Levy pada SMA di Kota Bandung - Angelica Apriliana; Achmad Samsudin; Raden Giovanni Ariantara (Mataram University, 2026)
A US-based Partnership for 21st Century Skills (P21) identifies 21st-century competencies through the 4Cs: critical thinking, collaboration, communication, and creativity. Communication is an essential competency in physics learning, particularly scientific communication, because students are required to express concepts, interpret data, and present scientific ideas systematically. This study aims to describe students’ scientific communication skills on heat and heat transfer using the Spector-Levy analysis at senior high schools in Bandung City. This study employed a survey method involving 34 students. The instrument was an essay test covering four aspects: scientific reading, scientific writing, listening and observing, and information representation. The data were analyzed based on mean scores and skill categories, supported by Rasch analysis to examine item quality and the relationship between students’ abilities and item difficulty. The results show that students’ scientific communication skills were generally in the moderate category, with different achievements across aspects. Information representation achieved the highest score, while listening and observing achieved the lowest. These findings indicate that students are relatively able to present information visually, but still have difficulty interpreting observations and connecting data with heat concepts. Therefore, problem-solving-based physics learning is needed to train students to analyze problems, justify explanations, and communicate scientific findings effectively.